Modern C++ for absolute beginners : a friendly introduction to the C++ programming language and C++11 to C++23 standards - Dmitrović, Slobodan (ITpro collection, 2023)
Learn the C++ programming language in a structured, straightforward, and friendly manner. This book teaches the basics of the modern C++ programming language, the C++ Standard Library, and modern C++ standards, including C++23. No previous programming experience is required. C++ is a language like no other, surprising in its complexity, yet wonderfully sleek and elegant in so many ways. It is also a language that cannot be learned by guessing, one that is easy to get wrong and challenging to get right. To overcome this, each section is filled with real-world examples that gradually increase in complexity. Modern C++ for Absolute Beginners, Second Edition teaches more than just programming in C++23. It provides a solid C++ foundation to build upon. The author takes you through the C++ programming language, the Standard Library, and C++11 to C++23 standard basics. Each chapter is accompanied by the right amount of theory and plenty of source code examples. You will work with C++23 features and standards, yet you will also compare and take a look into previous versions of C++. After reading this book, you'll be able to start programming in modern C++ standards. You will do so with plenty of relevant source code examples, freely available via a dedicated GitHub repository.